Chronic social instability in adult female rats alters social behavior, maternal aggression and offspring development. Issue 3 (31st January 2017) - Pittet, Florent; Babb, Jessica A.; Carini, Lindsay; Nephew, Benjamin C.
Abstract: We investigated the consequences of chronic social instability (CSI) during adulthood on social and maternal behavior in females and social behavior of their offspring in a rat model. CSI consisted of changing the social partners of adult females every 2–3 days for 28 days, 2 weeks prior to mating. Females exposed to CSI behaved less aggressively and more pro‐socially towards unfamiliar female intruders. Maternal care was not affected by CSI in a standard testing environment, but maternal behavior of CSI females was less disrupted by a male intruder. CSI females were quicker to attack prey and did not differ from control females in their saccharin consumption indicating, respectively, no stress‐induced sensory‐motor or reward system impairments. Offspring of CSI females exhibited slower growth and expressed more anxiety in social encounters. This study demonstrates continued adult vulnerability to social challenges with an impact specific to social situations for mothers and offspring.